The effects of time-restricted eating for patients with nonalcoholic fatty liver disease: a systematic review - Lin, Xiaoxiao; Wang, Shuai; Huang, Jinyu (Frontiers in Nutrition, 2024)
Nonalcoholic fatty liver disease (NAFLD) represents a significant global health concern. Numerous investigations have explored the implications of time-restricted eating (TRE) in the management of NAFLD. Therefore, the objective of our study is to conduct a systematic review to summarize and analyze all randomized controlled trials (RCTs) of TRE for patients with NAFLD. A thorough literature search was executed across Embase, Cochrane Library, and PubMed databases, covering all records from their inception until September 1, 2023. All clinical studies of TRE for NAFLD were summarized and analyzed. Our systematic review included four RCTs, encompassing a total of 443 NAFLD patients. These studies varied in sample size from 32 to 271 participants. The TRE intervention was consistently applied with an 8hour window, over durations ranging from 4 weeks to 12 months. The findings suggest that TRE could offer several health benefits for NAFLD patients, such as improved liver health indicators like liver stiffness and intrahepatic triglyceride (IHTG) levels. Consequently, TRE appears to be a promising dietary intervention for NAFLD patients. However, it is premature to recommend TRE for patients with NAFLD. The existing body of research on the effects of TRE in NAFLD contexts is limited, underscoring the need for further high-quality studies to expand our understanding of TRE's benefits in treating NAFLD. The ongoing clinical trials may provide more insights into the effects of TRE for NAFLD.